IDNLearn.com: Your go-to resource for finding precise and accurate answers. Ask your questions and receive detailed and reliable answers from our experienced and knowledgeable community members.
Sagot :
Answer:
h(x) = (x -1)(x +3+√2)(x +3-√2)
Step-by-step explanation:
You want the linear factors of h(x) = x^3 +5x^2 +x -7, given that 1 is a zero.
Quotient
If 1 is a zero, then (x -1) is a factor. The remaining quadratic factor can be found using synthetic division, as shown in the attachment. This tells us the factorization is ...
h(x) = (x -1)(x^2 +6x +7)
Quadratic factors
The factors of the quadratic can be found by completing the square:
x^2 +6x = -7
x^2 +6x +9 = 2 . . . . . . . add (6/2)^2 = 9 to both sides
(x +3)^2 = 2 . . . . . . . . show as a squre
x +3 = ±√2 . . . . . . . . take the square root
x +3 ±√2 = 0 . . . . . . subtract ±√2; the two remaining factors
This tells us that h(x) = 0 when (x +3 +√2) = 0 and when (x +3 -√2) = 0. These binomial expressions are the remaining linear factors of h(x).
h(x) = (x -1)(x +3+√2)(x +3-√2)
Thank you for using this platform to share and learn. Don't hesitate to keep asking and answering. We value every contribution you make. Your questions deserve accurate answers. Thank you for visiting IDNLearn.com, and see you again for more solutions.